SOCIAL MEDIA IMPACT ON UNIVERSITY REPUTATION AND ENROLLMENT: AN EMPIRICAL INVESTIGATION OF ONLINE PRESENCE AND STUDENT CHOICES - Abdol Ghani, Mohd Reza; Wan Mohamad Nawi, Wan Nurul Fatimah; Husain, Rosita (I-iECONS e-proceedings, 2023)
This study examines the influence of social media on university reputation and enrolment, specifically focusing on private universities in the Klang Valley. As digital communication continues to permeate every aspect of society, higher education institutions must adapt to remain competitive and attract prospective students. The primary objective of this research is to explore the relationship between a university's online presence and students' enrolment decisions. A quantitative survey method was employed, drawing a representative sample of students from private universities in the Klang Valley. Data were collected using a structured questionnaire that assessed students' perceptions of university reputation, social media usage, and the role of online presence in their enrolment choices. Preliminary findings indicate a positive correlation between an institution's social media presence and both its perceived reputation and enrolment rates. The study highlights the significance of effective social media strategies for private universities, emphasizing the need for institutions to leverage digital platforms to enhance their reputation and attract potential students. Further research is recommended to explore the long-term impact of social media on university performance and student success.